Νοn-Classical Paradigms in Contract Law in the American, European and Russian Legal Doctrines - KIRPICHEV, A. E.; SHAGIEVA, R. V.; NIKOLYUKIN, S. V.; BORISOVA, N. E.; RALKO, V. V. (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
Thematic justification: In many regions of the world, scholars have renewed a discussion on the nature and properties of contracts as a legal phenomenon, leading to the emergence of so-called ‘non-classical theories of contract’: contract as a promise, relational contract, contract as a network etc. This article’s aim is to compare non-classical approaches to contract and check the possibility of creating a modern holistic theory of contract. This article’s methodology is based on the functional method, the use of which provides a comparative perspective, meaning that each of the explored approaches to the theory of contract should be studied in the context of its causes and problems it solves. The article systematizes problems solved by non-classical theories of contracts and concludes that the development of a new theory means the appearance of a new solution, not only for the problem for which it was designed but also for some others from the list. No theory solves all the problems of contract law. Numerous theories of the 20th and 21st centuries have shown the directions, in which it is necessary to carry out research and to seek approaches whose combinations and mutual critical evaluations will allow the formation of a met theory of contract law, the further development of which can lead to a dominant paradigm shift in response to the emergence of an integrative legal theory of contract viewed in a holistic manner as a multifaceted phenomenon.